2009
DOI: 10.1080/08860220903050405
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ghrelin Immunoreactivity in Kidney Tissues of Diabetic Rats

Abstract: Backgrounds/Aims. Ghrelin, a recently discovered hormone, is released largely from stomach and might affect insulin secretion and glucose metabolism. The aim of this study was to determine the immunohistochemical localization of ghrelin in streptozotocin-induced diabetic rat kidneys. Methods. Fifty-four adult male Wistar rats were used in this study. All rats were divided into nine groups according to three time points of the study (2, 4, and 6 weeks) as control group, control group given 0.1 M phosphatecitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…In a study investigating the effect of enalapril and losartan on ghrelin immunoreactivity, it was shown that the immunoreactivity was significantly increased in the kidneys of diabetic rats (Donder et al 2013). Other studies showed that ghrelin immunoreactivity in the distal and collecting tubules was gradually increased with duration of diabetes (Yabuki et al 2006;Kuloglu and Dabak 2009). In the present study, ghrelin immunoreactivity was observed in the distal and collecting tubules in the control group, whereas it was also observed in the proximal tubules in the diabetes groups.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…In a study investigating the effect of enalapril and losartan on ghrelin immunoreactivity, it was shown that the immunoreactivity was significantly increased in the kidneys of diabetic rats (Donder et al 2013). Other studies showed that ghrelin immunoreactivity in the distal and collecting tubules was gradually increased with duration of diabetes (Yabuki et al 2006;Kuloglu and Dabak 2009). In the present study, ghrelin immunoreactivity was observed in the distal and collecting tubules in the control group, whereas it was also observed in the proximal tubules in the diabetes groups.…”
Section: Discussioncontrasting
confidence: 38%
“…Total and active ghrelin levels were significantly increased in STZ-induced diabetic rats (Masaoka et al 2003). It has been suggested that increased ghrelin levels in diabetes contributed to the pathogenesis of nephropathy by increasing GH levels (Kuloglu and Dabak 2009). However, there are unsatisfactory data on ghrelin and ghrelin receptor (GHSR-1a) mRNA expression levels in the diabetic kidney.…”
Section: Introductionmentioning
confidence: 83%